Atlas of time-temperature diagrams for nonferrous alloys - Vander Voort, George F (Materials data, 1991)
Aluminum-base alloys - Cobalt-base alloys - Copper-base alloys - Gold-base alloys - Magnesium-base alloys - Nickel-base alloys - Niobium-base alloys - Platonium-base alloys - Silver-base alloys - Titanium-base alloys - Uranium-base alloys - Zinc-base alloys - Zirconium-base alloys - Amorphous metals - Intermetallic compounds.